(untitled) (Fiep Bulletin - online, 2013)
Nowadays, the futsal is one of the most practiced sports by all parents, it can be found in a big part of the schools, it is a sport that fascinates and conquers, in an increasing number, many admirers; the physical aptitude related to health, which are minimum levels that a person should have to lead a life without many problems, is directly connected to the regular practice of systematic physical activity. This work was done in order to verify the level of physical aptitude linked to health in male children from 9 to 14 years. The study assessed the level of physical aptitude in health-related component of: muscular strength, muscular endurance, flexibility and body composition. For the evaluation, it was used as bases the tests’ battery Fitnessgram (1987) apud Morrow Jr. et al. (2003). And for body composition, it was used the BMR (Body Mass Rate) as the classification of Heyward (2004). And the study had two moments: at first, the proposed tests were applied; after the first test, the interference of the futsal classes with the student members of the sportive initiation at the school was done. And subsequently, in the second moment to the reapplication of the tests, with two months of interference. The study concluded that the children and teenagers are below the minimum levels in the variables flexibility and resistence, but they are within the expected levels regarding muscular strenght and body composition. It is suggested that further studies can be conducted in the future, seeking activit